Synthesis, molecular structure, experimental and theoretical characterization of 3-((2-(2,4-dinitrophenyl) hydrazone) methyl) pyridine- Carcinopreventive activity (in silico and in vitro investigation) - Vedhapriya, K.; Balaji, G.; Dhiyaneshwari, B.; Kumaran, S.; Narayana, B.; Kodlady, Suresh N; Kadaikunnan, Shine; Abbas, Ghulam; Muthu, S. (Journal of molecular structure, 2023)
•Experimental and theoretical FT-IR and FT-Raman spectra of DNPHMP have been analysed.•Electronic properties were studied for protic and aprotic solvents.•Chemical bonding and topological investigations have been studied.•In-Vitro studies of DNPHMP molecule with A549 cancer cell protein are done.•Protein-ligand docking is done for the biological investigation of drug designing. Schiff base compound 3-((2-(2, 4- Dinitrophenyl) hydrazone) methyl) pyridine (DNPHMP) has been synthesized and characterized. DNPHMP molecule was optimized using the B3LYP standard approach in combination with the 6–311++G (d, p) basis set. The Fukui function and MEP are used to identify the chemical reactive sites. Vibrational analysis was computed and investigated through experimental results. Fundamental frequencies and intensity of bands along with PED assignment are done. The HOMO-LUMO (electron donor and acceptor) plays an essential role in chemical stability and reactivity. The compound's experimental and computed electronic excitation state were analysed using UV–vis spectra with different solvents. Topological analysis (i.e., ELF, LOL, and RDG) is also analysed. NBO analysis is used to know about the bonding interactions between the molecules. NLO is done to verify the polarization properties of the compound. Drug likeness is obtained through the online portal. In vitro, studies of the synthesized compound are done against the A549 cell line. Both theoretical and experimental studies suggest that the DNPHMP molecule has Carcinopreventive activity against lung cancer cell line.